1979
DOI: 10.1093/jnci/63.3.797
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Tumors and Common Diseases in Three Types of Hamsters2

Abstract: Hamsters of three types designated as inbred cream (Epp/e/e), linebred white (EPP/cdcd/RB/A), and linebred albino (EPP/cdcde/e) were thoroughly examined histopathologically for spontaneous diseases. All hamsters were maintained simultaneously for life under identical standard laboratory conditions. Marked differences were found in longevity of the animals and in incidence, sites, patterns, and types of spontaneous diseases. In cream hamsters (CH), survival time was shorter than in white hamsters (WH) and albin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
35
1

Year Published

1981
1981
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(39 citation statements)
references
References 0 publications
3
35
1
Order By: Relevance
“…In a subsequent paper, the authors evaluated three strains of hamsters (strains CW, WH, and AH) from the Eppley Institute maintained under the same conditions. A direct relationship between age and the time of appearance of multiple tumors was evident (36). Polyps of the ceca were detected in all three groups of hamsters and were invariably associated with chronic proliferative colitis.…”
Section: Discussionmentioning
confidence: 79%
“…In a subsequent paper, the authors evaluated three strains of hamsters (strains CW, WH, and AH) from the Eppley Institute maintained under the same conditions. A direct relationship between age and the time of appearance of multiple tumors was evident (36). Polyps of the ceca were detected in all three groups of hamsters and were invariably associated with chronic proliferative colitis.…”
Section: Discussionmentioning
confidence: 79%
“…43, No. 2, 2015 NONNEOPLASTIC LESIONS IN SYRIAN HAMSTERSare found in 3 hamster strains (white, albino, and cream hamsters; Pour et al 1979). Acinar cell atrophy in the pancreas was noted at a moderate incidence in the long-term studies analyzed for this article.…”
Section: Discussionmentioning
confidence: 78%
“…Liver cysts and bile duct proliferation occurred in 3 strains of hamster (cream, white, and albino; Pour et al 1979) and are reported at MCINNES ET AL. TOXICOLOGIC PATHOLOGY a relatively high frequency (49-70%) in older male and female Han:AURA hamsters (Kamino et al 2001).…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations